Re/viewing Scholarly Publication of Panauti Journal and Punyawati Journal Published by Indreshwor Campus Panauti, Kavrepalanchok (Punyawati Journal, 2026)
This study re/viewed 36 articles which are published in three volumes of Panauti Journal and first volume of Punyawati Journal. The Journals are publication of Indreshwor Community Campus published between 2023 and 2025. The aim of the study was to assess academic contributions of Journals including scopes of research and overall quality and influence of the publications. The study used descriptive quantitative analysis along with inductive thematic analysis. The review finds that these publications cover multidisciplinary fields. The Journals getting better at being rigorous in methods and digging into multiple theories. Dependency theory, Marxist political economy, and Intersectional Feminism get applied from global ideas have been used for interpreting national issues of the country. The themes in the research unpack some evidence on contemporary issues such as the agrarian crisis, educational policies, labor migration patterns, and preserving cultural heritage. These issues help to develop evidence based policies to the federal government. The Journals strategically follow double-blind peer review and making everything open access through the NepJOL platform. On the global side, there are some good comparisons, especially about post-colonial development and changes in the Global South. Indreshwor Campus publishing effort feels like a landmark example of local academic work that could matter more widely. It pushes multidisciplinary fields and builds credibility for both researchers and the readers in practice. Finally, for getting better in the future, the re/view suggests receiving well-structured manuscripts, bringing in international editors, publishing special thematic issue, and building up internal citations by the authors. That might help to enrich quality of Journal publication.